Applying the attractor field model to social cognition perceptual discrimination is facilitated, but memory is impaired for faces displaying evaluatively congruent expressions. [article]. - Corneille, Olivier
A new model of mental representation is applied to social cognition : the attractor field model. Using the model, the authors predicted and found a perceptual advantage but a memory disadvantage for faces displaying evaluatively congruent expressions. In experiment 1, participants completed a same/different perceptual discrimination task involving morphed pairs of angry-to-happy Black and White faces. Pairs of faces displaying evaluatively incongruent expressions (i. e., happy Black, angry White) were more likely to be labeled as similar and were less likely to be accurately discriminated from one another than faces displaying evaluatively congruent expressions (i. e., angry Black, happy White). Experiment 2 replicated these finding and showed that objective discriminability of stimuli moderated the impact of attractor field effects on perceptual discrimination accuracy. In experiment 3, participants completed a recognition task for angry and happy Black and White faces. Consistent with the attractor field model, memory accuracy was better for faces displaying evaluatively incongruent expressions. Theoretical and practical implications of these findings are discussed.
Keywords: Stereotyping; Prejudice; Emotions; Face perception; Facer memory